Transformational Leadership Practices Among Music, Arts, Physical Education, and Health (MAPEH) Department Heads in Promoting Holistic Education - Nulud, Analiza (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the transformational leadership practices of MAPEH department heads and their influence on the promotion of holistic education in selected secondary schools. Specifically, it aimed to determine the level of transformational leadership practices in terms of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration; assess the level of promotion of holistic education in MAPEH across physical development, emotional and mental well-being, creative and artistic expression, and social and ethical growth; identify significant differences in the perceptions of teachers and department heads; examine the relationship between leadership practices and holistic education; and determine the challenges encountered by department heads in implementing leadership strategies. A descriptive-correlational research design was employed, utilizing survey questionnaires administered to teachers and MAPEH department heads. Data were analyzed using weighted mean, independent samples t-test, and Pearson r correlation. Findings revealed that transformational leadership practices were generally evident among department heads, with strengths in ethical leadership and motivation, but with areas for improvement in vision communication, innovation support, and recognition of teachers. Holistic education in MAPEH was rated positively across all domains, indicating that the subject contributes meaningfully to learners’ overall development. However, significant differences were found between the perceptions of teachers and department heads, with department heads consistently giving higher ratings. Furthermore, results showed a strong to very strong positive relationship between transformational leadership practices and holistic education, highlighting the critical role of leadership in enhancing instructional outcomes. The study also identified key challenges, including time constraints, resource limitations, and student-related concerns. The study concludes that while MAPEH effectively promotes holistic education, strengthening leadership practices, improving resource support, and aligning institutional expectations with classroom realities are essential to further enhance program implementation.
Keywords: Transformational Leadership, Holistic Education, MAPEH